Recent Trends in Multi-user MIMO Communications - Ben Zid, Maha (IntechOpen, 2013)
This book emphasis on multi-user MIMO communication. It covers a collection of the major topics and issues in multi-user MIMO systems. Recent Trends in Multi-user MIMO Communications provides a tutorial overview of the latest technologies and research keys related to multi-user communication. This book is composed of seven chapters, each written by a different set of authors. Features include: Fundamentals of multi-user MIMO communication, Random Beamforming in multi-user MIMO systems, LTE and LTE-Advanced framework, Interference cancellation in multi-user MIMO systems, Incorporation of multi-user capabilities in IEEE 802.11n/ac for WLAN systems, Physical layer security for multi-user MIMO communication, User selection based error probability of MIMO detector in multi-user MIMO systems.